A concepção de vontade nas questões 80 a 82 da prima pars da Summa Theologiae de Tomás de Aquino - Serra, Thiago de Souza (Universidade Federal de São Carlos, 2021)
Thomas Aquinas, in questions 80 to 82 of the Prima Pars of his Summa Theologiae, deals with sensitive appetites, the concupiscible and the irascible, and, above all, with the superior human appetite, the will. According to the Aquinate, this has as its own object the good produced since the intellectual apprehension of the essences of the particular entities (composed by matter and form) and, consecutively, presented to it by the human intellect. In this work, we will seek not only to understand the diversity between sensitive appetites and the will, but also the way in which it is related to its own object, that is, the intellectual good.
The conception of will in questions 80 to 82 of prima pars da Summa Theologiae de Tomás de Aquino
Keywords: Bem; Concupiscível; Intelecto; Irascível; Razão; Vontade; Good; Concupiscible; Intellect; Irascible; Reason; Will; CIENCIAS HUMANAS::FILOSOFIA::METAFISICA